EVALUATION OF ISLAMIC EDUCATION BASED ON TOLERANT CULTURE AT PUBLIC UNIVERSITY - Siti Mutholingah; Baharuddin Baharuddin; Basri Zain (STAI Ma'had Aly Al-Hikam Malang, 2023)
Evaluation in Islamic Education is something that is very urgent in order to know the success of the Islamic Education process. Public university has multi-religion and multicultural student conditions, so that an attitude of tolerance really needs to be developed. Because the evaluation of Islamic Education in public university also needs to be based on a culture of tolerance. The purpose of this study is to determine the scope, techniques and learning outcomes in evaluating ISLAMIC EDUCATION on campus. This study uses a qualitative approach. The results of this study are the coverage of ISLAMIC EDUCATION evaluation with a tolerant culture, namely cognitive, affective and psychomotor aspects, the evaluation technique uses test and non-test techniques, the learning outcomes include program achievements and student tolerant attitudes. The novelty of this research is the collaborative-participatory evaluation model.